Israel and the Palestinian Refugees
VIII, 501 p.
Keywords: This edited book offers diverse perspectives on the Palestinian refugee problem and the possible ways to facilitate its resolution. The book contains contributions of Israeli, Palestinian and other scholars, and its main goal is to initiate an informed dialogue that will bridge the “knowledge gap” between the different camps. The book is the cul- nation of a joint effort to assist people to realize how people on the other side envision the problem and the possible ways to resolve it, and to gain a comparative perspective on refugee problems and their reso- tion efforts in other parts of the world. The contributors come from - verse disciplines and backgrounds and their various contributions p- vide a comprehensive picture of the various aspects of the problem and of the possible means of its resolution. The Palestinian refugees problem is perhaps the most acute challenge to a peaceful settlement of the Israeli-Palestinian conflict. It is a challenge that scholars must address in a calm and detached manner, but at the same time a deeply emotional matter that even the most sophisticated scholars find difficult to engage without compromising their academic integrity. Despite these difficulties, we undertook the task of convening a meeting where the papers were presented and of the publication of this book because we think the contributions in this book provide p- spectives that contribute to the initiation of a constructive dialogue among the relevant communities.